Orang Asing Yang Berada Di Indonesia Berdasarkan Ketentuan Undang – Undang Nomor 6 Tahun 2011 Tentang Keimigrasian - Tita Jolanda Anggraini Sahetapy; Johanis Steny Franco Peilouw; Irma Halima Hanafi (LUTUR Law Journal, 2023)
Immigration is a matter of regulating the traffic of people entering or leaving the Territory of the Republic of Indonesia and its supervision in the context of maintaining state sovereignty. Purpose of the Research: Based on this, the problem in this writing is "How is the regulation of Law Number 6 of 2011 concerning Immigration of Foreigners in Indonesia". Methods of Research: Scientific writing is carried out using research methods, with normative juridical research types, problem approaches using case approaches and law approaches, primary, secondary and tertiary sources of legal materials and techniques for collecting and managing legal materials using library research by searching and reviewing books. related to solving the problem in this writing. Result of the Research: Foreigners who enter illegally into the territory of the State of Indonesia are foreigners who enter without going through the inspection of immigration officials and without being accompanied by valid and still valid travel documents, this is a development burden for the government in solving these problems. This can be seen and studied in the Immigration Act by looking at the arrangements for the supervision of foreigners and the imposition of sanctions on immigration crimes committed. Immigration in carrying out its duties and authorities must be more assertive in handling and providing sanctions to foreigners who commit immigration violations and crimes in accordance with Law No. in giving sanctions to someone who commits an immigration crime.